Navigating Crises and Ethical Evolution: The Role of Crisis Management and Corporate Social Responsibility in Modern Business Practices - Jyot Kota; Yash Bhanderi; Aryan Loriya; Chaksu Patel; Viral Patel; Rahul Chauhan; Andino Maseleno; R Rizal Isnanto (Greenation International Journal of Law and Social Sciences, 2023)
This study explores the influence of demographic factors—age, gender, and occupation—on employees’ perceptions of crisis management and corporate social responsibility (CSR). Using ANOVA analysis, the research evaluates how these factors impact opinions on organizational crises, management performance, communication strategies during crises, and the role of CSR in business operations. The findings indicate that occupation significantly affects perceptions of management crises and CSR initiatives, while age and gender have minimal impact. The study highlights the need for organizations to adopt tailored approaches to crisis management and CSR, considering diverse occupational perspectives. It also emphasizes that strategic crisis response and CSR integration are essential for business resilience and sustainability. Future research could explore the impact of cultural and sectoral differences, as well as the influence of digital transformation and ESG practices. These insights will help organizations enhance their global impact through adaptive crisis management and socially responsible practices.